Improving Digital Competence of Elementary School Teachers through Context-Based ICT Learning Assistance in the Southern Peripheral Area of Jember - Mu'afifah Mu'afifah; Fajar Siddiq Setiawan (Unity Academy, 2026)
This community service program aims to enhance the digital competence of elementary school teachers in the southern peripheral area of Jember Regency through context-based ICT learning assistance. A total of 30 teachers from three elementary schools participated in the program. Teachers in peripheral areas often face limited digital infrastructure, minimal training opportunities, and low confidence in using technology for instructional purposes. This program applied a participatory mentoring model consisting of digital literacy workshops, guided practice, classroom implementation, and reflective evaluation. Data were collected using observation sheets, competency questionnaires, and documentation of teachers' digital learning products. The results indicate a substantial improvement in teachers' digital competence across all indicators: fundamental digital literacy increased by 40 percentage points (from 45% to 85%), learning management system integration improved by 42 percentage points (from 38% to 80%), and interactive digital media development rose by 48 percentage points (from 30% to 78%). The novelty of this program lies in the integration of contextual mentoring, peer collaboration, and locally adaptive digital tools tailored to peripheral school conditions. The program produced tangible outputs, including teacher-created digital learning media, instructional modules, and increased readiness to implement blended learning. This community service contributes to strengthening teacher professionalism and reducing the digital divide in elementary education within peripheral regions.